(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
The article discusses the activity of microorganisms in soils, their role in increasing soil fertility, symbiotic relationships, and the process of nitrogen fixation. Information about nitrogen-fixing bacteria and their characteristics is provided.